Conceptual Framework of Innovative Library Services Based on Artificial Intelligence (AI) in Order to Accelerate Digital Transformation - Subchan, Nur (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2024)
Background: The Fourth Industrial Revolution (4IR) refers to the transformation of traditional production processes that have been digitized into the real world, enabling total interconnectivity between suppliers and customers with the aim of creating smarter products. The rapid changes in technology brought about by the 4IR have made business operations unstable. This has led to organizations seeking new methods and strategies to gain a competitive advantage in this digital age. Institutions of higher education have responded to this challenge by strengthening the role of university libraries as core components of the educational institution. They have also introduced various digital technologies to improve the learning experience for students.Methods: qualitative content analysis.Purpose: organizations to seek new methods and strategies to gain a competitive advantage in the digital era.Findings: Artificial Intelligence (AI) is one of the technologies that can be integrated into university libraries to enhance the learning experience for students. AI is a discipline that involves computer science, linguistics, information science, neurophysiology, neuroscience, cognitive science, psychological control, and other fields. AI is not just a computer program that mimics human intelligence but can also be used to promote independent learning and meet the special needs of all categories of students. With the support of large amounts of data, AI can form patterns and provide meaning, making the university library an ideal environment to apply this technology to add value to higher education in the future.Conclusion: The integration of AI into university libraries can provide an opportunity for every library user to access new and exclusive educational services specifically designed to meet individual student needs. Assuming that the library is supported by AI technology, it can help improve learning skills through more personalized technical learning approaches. AI technology can also help librarians explore new ways to meet the needs of library users and support academic activities. By utilizing AI technology, the library can provide sustainable access to various online text resources that are rapidly expanding, and provide services that are not limited to conventional boundaries, accessible to anyone and from anywhere. ABSTRAK Kerangka Konseptual Layanan Inovatif Perpustakaan Berbasis Artificial Intelligence (AI) dalam Rangka Mempercepat Transformasi Digital Latar Belakang: Revolusi Industri keempat (The Fourth Industrial Revolution - 4IR) merujuk pada transformasi proses kegiatan konvensional yang telah didigitalisasi ke dalam dunia nyata, memungkinkan interkoneksi secara total antara pemasok dan pelanggan dengan tujuan menciptakan produk yang lebih cerdas. Perubahan teknologi yang cepat yang dibawa oleh 4IR membuat operasi bisnis menjadi tidak stabil. Hal ini mendorong organisasi untuk mencari metode dan strategi baru untuk memperoleh keunggulan kompetitif di era digital ini. Institusi pendidikan tinggi telah menanggapi tantangan ini dengan memperkuat peran perpustakaan perguruan tinggi sebagai komponen inti dari lembaga Pendidikan. Perguruan Tinggi juga telah memperkenalkan berbagai teknologi digital untuk meningkatkan pengalaman belajar bagi mahasiswa. Metode: analisis konten kualitatif. Tujuan: organisasi untuk mencari metode dan strategi baru untuk memperoleh keunggulan kompetitif di era digital. Temuan: Kecerdasan Buatan (AI) adalah salah satu teknologi yang dapat diintegrasikan ke dalam perpustakaan perguruan tinggi untuk meningkatkan pengalaman belajar bagi mahasiswa. AI merupakan disiplin ilmu yang melibatkan ilmu komputer, linguistik, ilmu informasi, neurofisiologi, neurosains, ilmu kognitif, kontrol psikologis, dan bidang lainnya. AI bukan hanya program komputer yang meniru kecerdasan manusia, tetapi juga dapat digunakan untuk meningkatkan pembelajaran mandiri dan memenuhi kebutuhan khusus semua kategori mahasiswa. Dengan dukungan data yang besar, AI dapat membentuk pola dan memberikan makna, menjadikan perpustakaan perguruan tinggi lingkungan yang ideal untuk menerapkan teknologi ini untuk menambah nilai pada pendidikan tinggi di masa depan.Kesimpulan: Integrasi AI ke dalam perpustakaan perguruan tinggi dapat memberikan kesempatan bagi setiap pengguna perpustakaan untuk mengakses layanan pendidikan baru dan eksklusif yang dirancang khusus untuk memenuhi kebutuhan individu mahasiswa. Hal tersebut dapat diasumsikan bahwa perpustakaan didukung oleh teknologi AI, dapat membantu meningkatkan keterampilan belajar melalui pendekatan pembelajaran teknis yang lebih personal. Teknologi AI juga dapat membantu pustakawan mengeksplorasi cara baru untuk memenuhi kebutuhan pengguna perpustakaan dan mendukung kegiatan akademik. Dengan memanfaatkan teknologi AI, perpustakaan dapat menyediakan akses berkelanjutan ke berbagai sumber teks online yang terus berkembang, serta memberikan layanan yang tidak terbatas dan dapat diakses oleh siapa saja dan dari mana saja.